2019
DOI: 10.1007/s12192-019-01008-9
|View full text |Cite
|
Sign up to set email alerts
|

Hippo/Mst1 overexpression induces mitochondrial death in head and neck squamous cell carcinoma via activating β-catenin/Drp1 pathway

Abstract: Mammalian Ste20-like kinase 1 (Mst1) is associated with cell apoptosis. In the current study, we explored the regulatory effects of Mst1 on squamous cell carcinoma of the head and neck (SCCHN) in vitro. SCCHN Cal27 cells and Tu686 cells were transfected with adenovirus-loaded Mst1 to detect the role of Mst1 in cell viability. Then, siRNA against Drp1 was transfected into cells to evaluate the influence of mitochondrial fission in cancer survival. Our data illustrated that Mst1 overexpression promoted SCCHN Cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 62 publications
(61 reference statements)
3
8
0
Order By: Relevance
“…Besides inhibiting DRP1 phosphorylation, Mdivi-1 down-regulated DRP1 expression in this study. As reported by other authors 32,38 , inhibition of DRP1 by Mdivi-1 decreased the DRP1 expression in their experiments. Mdivi-1 is reported to have additional targets, which may be responsible for DRP1 down-regulation.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Besides inhibiting DRP1 phosphorylation, Mdivi-1 down-regulated DRP1 expression in this study. As reported by other authors 32,38 , inhibition of DRP1 by Mdivi-1 decreased the DRP1 expression in their experiments. Mdivi-1 is reported to have additional targets, which may be responsible for DRP1 down-regulation.…”
Section: Discussionsupporting
confidence: 87%
“…DRP1 is essential in mitochondrial fission and mitophagy initiation. Some studies have illustrated the existence of cytosolic Ca 2+ /DRP1 or Wnt/β-catenin/DRP1 axis in mitochondrial function regulation for cancer [31][32][33] . Multiple posttranslational modifications of phosphorylation, ubiquitination and sumoylation regulate the functions of DRP1 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, overexpressed Mst1 caused mitochondria-dependent breast cancer cell apoptosis via the JNK–Drp1 pathway [ 60 ]. Another study reported the tumor-suppressive effects of Mst1 on cancer cell proliferation and metastasis by activating the β -catenin/Drp1 axis [ 61 ]. Furthermore, Mst1 overexpression impaired the proliferation and migration of colorectal cancer cells by activating the JNK/ p 53/Bnip3 pathway [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mst1 overexpression causes apoptosis by increasing ROS generation, the levels of the Bax proapoptotic protein, and the activity of caspase-9, while decreasing the antioxidant activity of SOD, GSH, and GPX, as well as the levels of the antiapoptotic protein Bcl-2 in the squamous cell carcinoma of the head and neck (SCCHN) Cal27 cell line and in Tu686 cells; the mechanism is thought to involve the regulation of mitochondrial fission via the β-catenin/DRP1 pathways [ 254 ]. An inhibition of the Wnt/β-catenin pathway by DKK1 was already reported to lower Mst1-mediated DRP1 upregulation, and therefore apoptosis, in Cal27 and Tu686 cells [ 254 ].…”
Section: Proapoptotic Effect Of the Wnt/β-catenin Pathway In Cancer Cellsmentioning
confidence: 99%